The two-parameter method of optimal extrapolation of random nonstationary signals on the background noise - Ігнатов, В. О.; Андреєв, О. В.; Андреєв, В. І (Problems of Informatization and Control, 2010)
A new method of extrapolation of stationary random processes on the background noise, which uses the two previous discrete signal values and their values has the best extrapolation for the third time in the future